Smooth Al nanolayers deposition on sapphire and quartz substrates - Wróbel, Piotr; Stefaniuk, Tomasz; Ciesielski, Arkadiusz Sylwester; Szoplik, Tomasz (Photonics Letters of Poland, 2013)
We report on roughness of 70nm thick Al films deposited on fused silica and sapphire substrates using e-beam physical vapour deposition (PVD) system with exact control of substrates temperature. Before evaporation both types of epi-polished substrates are cleaned using low-energy Argon ion bombardment. The roughness of films deposited at 450, 297, 170 and 92K is measured with atomic force microscope (AFM). The lowest average root mean square (RMS) roughness equal 0.98 nm is obtained for 70nm Al film on sapphire deposited at 170K. Full Text: PDF References D. Sarid, W. Challener, Modern Introduction to Surface Plasmons (Cambridge, Cambridge University Press, 2010). D.M. Mattox, Handbook of Physical Vapor Deposition (PVD) Processing (Amsterdam, Elsevier, 2010). J. M. Pitarke, V.M. Silkin, E.V. Chulkov, P.M. Echenique, "Theory of surface plasmons and surface-plasmon polaritons", Rep. Prog. Phys. 70, 1 (2007). CrossRef E. Ozbay, "Plasmonics: Merging Photonics and Electronics at Nanoscale Dimensions", Science 311, 189 (2006). CrossRef S. Linic, P. Christopher, D.B. Ingram, "Plasmonic-metal nanostructures for efficient conversion of solar to chemical energy", Nature Materials 10, 911 (2011). CrossRef M. Castro-Lopez, D. Brinks, R. Sapienza, N. F. van Hulst, "Aluminum for Nonlinear Plasmonics: Resonance-Driven Polarized Luminescence of Al, Ag, and Au Nanoantennas", Nano Lett. 11, 4674 (2011). CrossRef T.J. Antosiewicz, P. Wróbel, T. Szoplik, "Performance of Scanning Near-Field Optical Microscope Probes with Single Groove and Various Metal Coatings", Plasmonics 6, 11 (2011). CrossRef O.J.F. Martin, M. Paulus, "Influence of metal roughness on the near-field generated by an aperture/apertureless probe", J. Microscopy 205, 147 (2002). CrossRef M.A. Ordal, L.L. Long, R.J. Bell, S.E. Bell, R.W. Alexander, Jr., C.A. Ward, "Optical properties of the metals Al, Co, Cu, Au, Fe, Pb, Ni, Pd, Pt, Ag, Ti, and W in the infrared and far infrared", Appl. Opt. 22, 1099 (1983). CrossRef H. Liu, Y.F. Zhang, D.Y. Wang, M.H. Pan, J.F. Jia, Q.K. Xue, "Two-dimensional growth of Al films on Si(1 1 1)-7 × 7 at low-temperature", Surf. Sci. 571, 5 (2004). CrossRef Y.H. Yu, Z. Tang, Y. Jiang, K.H. Wu, E.G. Wang, "Thickness dependence of the surface plasmon dispersion in ultrathin aluminum films on silicon", Surf. Sci. 600, 4966 (2006). CrossRef Y.Y. Cheng, C.C. Lee, "Simulation of molecular dynamics associated with surface roughness on an Al thin film", Surface & Coatings Technol. 203, 918 (2008). CrossRef H.J. Qin, Y. Jiang, G.H. Zhang, K.H. Wu, "Interaction of surface and interface plasmons in extremely thin Al films on Si(111)", Appl. Phys. Lett. 102, 051605 (2013). CrossRef T. Stefaniuk, P. Wróbel, T. Szoplik, Deposition of ultrasmooth silver nanolayers at pressures and temperatures above the sublimation point of water ice, ICTON 2013, NSON Session Proceedings (2013).